Digital Strategies for Promoting Religious Moderation: The Role of Muhammadiyah and Nahdlatul Ulama on Social Media - Yusuf, Muhammad Zulfikar; Nahar, Muhammad Hasnan; Abror, Hizba Muhammad; Renaldi, Muhammad Hafizh (International Journal of Nusantara Islam, 2024)
Indonesia is unique because of its pluralistic and diverse character. This uniqueness can certainly produce conflict between communities if not managed well. One cause of this is radicalism and intolerance. Moreover, there has been an increase in the number of digital media users in Indonesia, which has the potential to become an arena for contesting various ideologies, including extreme ones. Therefore, a country with religious and cultural diversity requires a religious moderation approach to overcome radicalism and intolerance. This study aims to provide an overview of the role of Muhammadiyah and Nahdlatul Ulama in promoting religious moderation on social media. The research method used was descriptive qualitative with descriptive analysis that uses secondary data from various scientific literature sources such as journals, books, official reports, and social media content. Muhammadiyah and Nahdlatul Ulama were chosen because they are the most prominent Islamic organisations in Indonesia and significantly influence religious life. Content analysis was used in this study. This research shows that religious organisations such as Muhammadiyah and Nahdlatul Ulama play an important role in efforts to ground the religious moderation movement in Indonesia, especially in the context of digital media. Islam Berkemajuan and Islam Nusantara are views initiated by these two organizations to foster religious moderation in society. These two organisations use digital platforms to spread religious messages that emphasise tolerance, harmony, and respect for diversity. The implication of this research is that the presence of Muhammadiyah and NU on social media is strategic in shaping public opinion and expanding the understanding of religion. By using digital media, these two organisations are disseminators of moderate religious teachings and agents of social change that can reduce extremism